2015
DOI: 10.1016/j.jadohealth.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of It's Your Game-Tech: A Computer-Based Sexual Health Education Program for Middle School Youth

Abstract: Purpose Few computer-based HIV, sexually transmitted infection (STI), and pregnancy prevention programs are available, and even fewer target early adolescents. In this study, we tested the efficacy of It’s Your Game (IYG)-Tech, a completely computer-based, middle school sexual health education program. The primary hypothesis was that students who received IYG-Tech would significantly delay sexual initiation by ninth grade. Methods We evaluated IYG-Tech using a randomized, two-arm nested design among 19 schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(138 citation statements)
references
References 27 publications
(32 reference statements)
1
110
1
7
Order By: Relevance
“…Findings indicated that IYG-Tech impacted some determinants of sexual behavior (e.g. STI and condom knowledge, attitudes about abstinence, condom use self-efficacy) but did not impact sexual behaviors or sexual initiation (62). Unique aspects: school-based sample of middle school youth (mean age 14.3), predominantly minority (74% Hispanic (English speaking) and 17% African American).…”
Section: Technology Interventions For Hiv Among Youthmentioning
confidence: 97%
“…Findings indicated that IYG-Tech impacted some determinants of sexual behavior (e.g. STI and condom knowledge, attitudes about abstinence, condom use self-efficacy) but did not impact sexual behaviors or sexual initiation (62). Unique aspects: school-based sample of middle school youth (mean age 14.3), predominantly minority (74% Hispanic (English speaking) and 17% African American).…”
Section: Technology Interventions For Hiv Among Youthmentioning
confidence: 97%
“…Se observa una mejora estadísticamente significativa en las actitudes hacia el uso del preservativo y la píldora anticonceptiva poscoital al mes y a los 6 meses de la intervención. (p < 0,05)PositivoGonzález et al 26 201369 adolescentes con edades entre 12 y 15 añosSe obtiene una mejora significativa posterior a la intervención para las conductas de riesgo de un embarazo en la adolescencia (p = 0,022) y para el nivel de conocimiento sobre sexualidad (p < 0,01)PositivoShegog et al 27 200714 adolescentes con edades entre 12 y 14 añosSe encuentran mejoras significativas en el conocimiento sobre sexualidad, conocimiento sobre enfermedades de transmisión sexual e importancia de un buen entorno de amistad (p < 0,05)PositivoPeskin et al 28 20151.374 adolescentes (768 grupo intervención y 606 grupo control), con edades entre 14 y 15 añosNo se encuentran diferencias significativas para las variables de iniciación sexual (p > 0,05), sin embargo, sí hay diferencias significativas para el nivel de conocimiento y uso del preservativo (p < 0,01), importancia de la abstinencia e importancia de los amigos (p < 0,05)PositivoAutorAñoMuestraPrincipales resultadosSentidoHernández Millán et al 29 2015180 adolescentes mujeres con edades entre 14 y 15 añosSe obtiene una mejora significativa posterior a la intervención en el nivel de conocimiento para conocimiento sobre las relaciones sexuales y sus riesgos (p < 0,05), para el nivel de conocimiento sobre enfermedades de transmisión sexual, métodos anticonceptivos (p < 0,01). Cuando se valora el nivel de conocimiento para la prevención del embarazo en la adolescencia se halla una mejora significativa (p < 0,01)EducativaTaylor et al 30 2014679 adolescentes con edades entre 13 y 16 añosSe obtiene que hay menos estudiantes que tienen actitudes positivas hacia el embarazo en la adolescencia (p < 0,01), mayor cantidad quiere abstenerse de relaciones hasta finalizar la escuela (p < 0,05), mayor comunicación hacia los padres (p < 0,05) y una mayor proporción de estudiantes usando anticonceptivos (p < 0,01)PositivoBonell et al 31 2013180 adolescentes en el grupo intervención y 180 en el control.…”
Section: Resultsunclassified
“…Cambio en el nivel de conocimiento: se seleccionaron 13 investigaciones17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, hallando todas una mejora significativa del nivel de conocimiento de los participantes.…”
Section: Resultsunclassified
“…Out of 22 studies, 4 (18%) involved users via interviews [65-68], 2 (9%) via classroom discussions [58,69], and 1 (5%) via a survey [70]. In 3 studies out of 22 (14%), a user technical advisory board was established [55,57,62], and in 3 studies (14%) reported in 2 papers, target group users were recruited as members of the design team [70,71]. …”
Section: Resultsmentioning
confidence: 99%
“…Users were recruited via purposive sampling in 12 out of 22 studies (55%) [51-54,58,59,61,65,68,69,71], via a self-selected convenience sample (eg, flyers) in 8 studies out of 22 (36%) [55-57,60,62,63,66,70], and/or via snowball sampling in 4 out of 22 studies (18%) [55,57,62,64]. For one study, no information could be obtained on sampling method [67].…”
Section: Resultsmentioning
confidence: 99%